PENGARUH SULFUR DIOKSIDA (SO2) PADA UDARA AMBIEN TERHADAP RISIKO KEJADIAN PNEUMONIA PADA BALITA - Fachmi Al Farisi; Budiyono Budiyono; Onny Setiani (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
Air pollution in Jakarta was the worst in Indonesia. There were 26 points classified into unhealthy concentration and East Jakarta being one of them. Sulfur dioxide (SO2) as 54.21 μg/Nm3 majorly contribute to the air pollution. The case of pneumonia in East Jakarta was the highest case with 2411 events. This study aimed to analyze the relationship between the concentrations of air pollutant of SO2 and the number of pneumonia incidence in children under-5 years of age.This research was an observational analytic approach with time-based ecological design. The research location was determination based on the coverage of The 4th Jakarta Monitoring Station. The incidence of pneumonia data were sourced from the secondary data of Health Surveillance Data in primary health care at Cipayung Sub-district, East Jakarta. Statistical analysis was performed by multiple linear regression test (α = 5%).The monthly average of SO2 was 41.55 μg/Nm3 and pneumonia incidences was 151 events. There was a significant corelation of SO2 with the number of pneumonia incidence in children under-5 years of age (p = 0,001).This research concluded that there was a contribution from sulfur dioxide to the number of pneumonia incidence in children under-5 years of age in Cipayung Sub-district, East Jakarta.